Protein Truncating Variants of colA in Clostridium perfringens Type G Strains - Van Damme, Lore; Cox, Natasja; Callens, Chana; Dargatz, Michelle; Flügel, Monika; Hark, Sarah; Thiemann, Frank; Pelzer, Stefan; Haesebrouck, Freddy; Ducatelle, Richard; Van Immerseel, Filip; Goossens, Evy (Frontiers in Cellular and Infection Microbiology, 2021)
Extracellular matrix (ECM) degrading enzymes produced by Clostridium perfringens may play an important role during the initial phases of avian necrotic enteritis by facilitating toxin entry in the intestinal mucosa and destruction of the tissue. C. perfringens is known to produce several ECM-degrading proteases, such as kappa toxin, an extracellular collagenase that is encoded by the colA gene. In this study, the colA gene sequence of a collection of 48 C. perfringens strains, including pathogenic (i.e. toxinotype G) and commensal (i.e. toxinotype A) chicken derived strains and strains originating from other host species, was analyzed. Although the colA gene showed a high level of conservation (>96% nucleotide sequence identity), several gene variants carrying different nonsense mutations in the colA gene were identified, leading to the definition of four truncated collagenase variant types (I-IV). Collagenase variant types I, III and IV have a (nearly) complete collagenase unit but lack parts of the C-terminal recruitment domains, whereas collagenase variant types II misses the N-terminal part of collagenase unit. Gene fragments encoding a truncated collagenase were mainly linked with necrotic enteritis associated C. perfringens type G strains with collagenase variant types I and II being the most prevalent types. Gelatin zymography revealed that both recombinant full-length and variant type I collagenase have active auto-cleavage products. Moreover, both recombinant fragments were capable of degrading type I as well as type IV collagen, although variant type I collagenase showed a higher relative activity against collagen type IV as compared to full-length collagenase. Consequently, these smaller truncated collagenases might be able to break down collagen type IV in the epithelial basement membrane of the intestinal villi and so contribute to the initiation of the pathological process leading to necrotic enteritis.